PROSEDUR PENYELESAIAN KREDIT BERMASALAH PADA PT BANK MANDIRI (PERSERO) Tbk KANTOR CABANG PEMBANTU TIMIKA HASANUDDIN - Alberton Tampubolon; Muh. Sabir (JURNAL ULET (Utility, Earning and Tax), 2018)
The aim of this research to determine the causes of the occurrence of nonperforming loans and know the troubled credit settlement procedures and what steps or procedures undertaken by PT Bank Mandiri (persero) Tbk HasanuddinTimika auxiliary branch office in completing the non-performing loans. This research is a descriptive research. data were collected through interviews of employee of PT Bank Mandiri sub-branch office of TimikaHasanuddin who has competency in the field of credit. Documentation of various documents related to research and literature collecting data through books to obtain data and theoretical concepts. To find out the troubled loan settlement procedure at PT Bank Mandiri (persero) Tbk, the HasanuddinTimika sub-branch office, the calculation loan collectibility, non performing loan (NPL) is performed (restructuring), sale, collateral auction, and write off. The result of this research showed that settlement procedure at PT Bank Mandiri (persero) Tbk, the HasanuddinTimika sub-branch office with implementation credit restructuring sale/auction collateral and write off,The implementation of restructuring by PT Bank Mandiri (persero) Tbk branch offices of TimikaHasanuddin through stages of credit file research, sending warning letters, restructuring decisions, and monitoring. The pattern or restructuring actions conducted to the debtorinclude the extension of the credit term, the reduction of interest arrears. The implementation of sale of collateral auction shall be done if the costumer’s business has no prospect to be developed while the application of write off is done when the debtor has collectibility 5 stuck and there is no transaction for 210 days at the time of the write off proposal.